Efektivitas Model Pembelajaran Pencapaian Konsep dengan Pendekatan Ilmiah terhadap Kemampuan Komunikasi Matematis Siswa pada Materi Fungsi Kelas VIII SMP Negeri 1 Berastagi - Atania Christianti Br Ginting (Neolectura, 2021)
This study is against the background of low students' mathematical communication skills. This study aims to determine the effectiveness of concept achievement model with scientific approach to students' mathematical communication skills in the function material of grade VIII SMP Negeri 1 Berastagi. This research is a quasi-quantitative research experiment. The sample technique used is cluster random sampling obtained class VIII-1 as an experimental class. Indicators of learning effectiveness used by researchers are 1) the quality of learning; 2) the level of learning. This study uses post-test instruments of learning results in the form of essays and observation sheets of teachers' similar teaching with the learning model used. Based on the regression analysis test obtained the regression equation Y= 16,230 + 0,783X, which means that both variables have a positive linear relationship. For the meaning of the correlation coefficient of communication ability obtained t table = 2,04 and t count = 16,368 which is the t count > t table. So the testing of the hypothesis of reject H0 and Ha accepted, then there is a strong and meaningful relationship between the learning model of concept achievement to the mathematical communication skills of students. Then the coefficient of determination obtained r^2= 89,93% means that there is a contribution of concept achievement learning model with scientific approach to the mathematical communication skills of students on function teaching materials by 89.93% so that based on learning quality indicators, the learning model is said to be effectively used. Based on the results of active observations of teacher activities obtained a total average of 4.26 which means the uniformity of teachers teaching with a model of learning concept achievement with a scientific approach is good and effective to the mathematical communication skills of students